The use of ant-plant (Myrmecodia pendans) as feed additive to broilers chicken - Iis Yuanita; L Silitonga; Paulini . (Jurnal Ilmu Ternak dan Veteriner, 2014)
Ant-plant (Myrmecodia pendans) is a unique plant which is widely used in Central Kalimantan and contains antioxidant flavonoids and tannin. The use of herbs as organic materials may produce good performance and carcass of chicken. The experiment used 40 Ross strain day old chicks which were randomly divided into 5 treatments and 4 replicates. The treatments were T0 (basal diet as a control), T1 (basal diet+0.1% ant-plant), T2 (basal diet+0.2% ant-plant), T3 (basal diet+0.3% ant-plant) and T4 (basal diet+0.4% ant-plant). Data were collected during 35 days to obtain feed intake, body weight gain, feed conversion, final body weight, mortality, carcass percentage and performance index. The data were analyzed for variances based on a Completely Randomized Design and continued with Duncan’s Multiple Range Test for differences. The result showed no significant effect of treatments on the performances, but T1 treatment (containing 0.1% ant-plant) showed good tendency to gain body weight, final body weight, carcass percentage and performance index respectively 0.51%; 0.44%; 0.15%; and 3.09% higher than T0 (control). It also showed good feed efficiency with feed conversion of value 2.43% lower than control. In conlusion, ant-plant as feed additive until 0.4% in broiler diet had no effect to improve broiler performances.Key Words: Broiler, Ant-Plant (Myrmecodia pendans), Feed Additive, Performance